That Rune Will Unlock Time’s Labyrinth…: Old Norse Themes and Motifs in George Mackay Brown’s Poetry - Ruseckienė, Rasa (Scandinavistica Vilnensis, 2019)
George Mackay Brown (1921–1996), an Orcadian poet, author and dramatist, was undoubtedly one of the finest Scottish creative voices of the twentieth century. He was greatly influenced by Old Norse literature, and this is reflected in his writings in many ways. The present article aims to trace and discuss Old Norse themes and motifs in Brown’s poetry. His rune poems, translations of the twelfthcentury skaldic verse, experimentation with skaldic kennings, as well as choosing saga personalities, such as Saint Magnus, Earl Rognvald of Orkney and others, as protagonists of the poems show the poet’s in-depth interest in the historical and literary legacy of his native Orkney and Old Norse culture in general.
Keywords: George Mackay Brown; Orkney; runic inscriptions; Orkneyinga saga; Saint Magnus; Earl Rognvald of Orkney; Vinland sagas; skaldic poetry; kennings